Comparative Productive Performance of Local Hens in Erbil- Kurdistan Region - Abas, Kamaran A.; Hermiz, Hani N.; Al-Khatib, Tahir R.; Amin, Shayma M.; Ahmed, Aram M.; Hamad, Dastan A. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This experiment was conducted to study the effect of age at production and different genetic phenotypes of local hens in Erbil. Birds of each genotype were kept in family pens depended on their colours (Line 1 = Black with Brown Neck, Line 2 = Isa Brown, Line 3 = Spotty, Line 4= Pure Black) were randomly distributed on two replicates compared with a commercial strain (Isa brown). Performance characteristics were evaluated. Results showed that age at production and genetic phenotype were affected significantly (P<0.05) on some performance traits. Significant differences between groups were found in Egg Production, Egg Mass, Feed Intake and Feed Conversion Ratio traits. Insignificant differences were found between groups in Egg Weight. Age of production affected insignificantly on Feed Intake, while affected significantly (P<0.05) on other traits. It is concluded that selection might be possible in local hens to improve their genetic potentials in Iraq-Kurdistan region.
Keywords: Local hens Egg production egg weight egg mass feed intake feed conversionratio